Challenging non-traumatic posterior urethral strictures treated with urethroplasty: a preliminary report - Lumen,Nicolaas (2009)
Introduction: Posterior urethral strictures after prostatic radiotherapy or surgery for benign prostatic hyperplasia (BPH) refractory to minimal invasive procedures (dilation and/or endoscopic urethrotomy) are challenging to treat. Published reports of alternative curative management are extremely rare. This is a preliminary report on the treatment of these difficult strictures by urethroplasty. Materials and Methods: Seven cases were treated: 4 cases occurred after open prostatectomy or transurethral resection of the prostate for BPH, one case after external beam irradiation and 2 after brachytherapy. The 4 cases after BPH-related surgery were in fact complete obstructions at the bladder neck and the membranous urethra with the prostatic urethra still partially patent. Anastomotic repair by perineal route was done in all cases with bladder neck incision in the BPH-cases and prostatic apex resection in the radiotherapy cases. Results: Mean follow-up was 31 months (range: 12-72 months). The operation was successful, with preserved continence, in 3 of the 4 BPH-cases and in 2 of the 3 radiotherapy cases. An endoscopic incision was able to treat a short re-stricture in the BPH-patient and a longer stricture at the bulbar urethra could be managed with a perineostomy in the radiotherapy-patient. Conclusion: Posterior non-traumatic strictures refractory to minimal invasive procedures (dilation/endoscopic urethrotomy) can be treated by urethroplasty using an anastomotic repair with a bladder neck incision if necessary.